2013
DOI: 10.1097/fjc.0b013e31828780eb
|View full text |Cite
|
Sign up to set email alerts
|

Human Electrophysiological and Pharmacological Properties of XEN-D0101

Abstract: The human electrophysiological and pharmacological properties of XEN-D0101 were evaluated to assess its usefulness for treating atrial fibrillation (AF). XEN-D0101 inhibited Kv1.5 with an IC50 of 241 nM and is selective over non-target cardiac ion channels (IC50 Kv4.3, 4.2 μM; hERG, 13 μM; activated Nav1.5, >100 μM; inactivated Nav1.5, 34 μM; Kir3.1/3.4, 17 μM; Kir2.1, >>100 μM). In atrial myocytes from patients in sinus rhythm (SR) and chronic AF, XEN-D0101 inhibited non-inactivating outward currents (Ilate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 21 publications
5
37
0
3
Order By: Relevance
“…Mathematical simulations support these findings and suggest that I Kur blockers with rapid binding or slow unbinding kinetics have the strongest antiarrhythmic effects (22,29 Consistent with this study, XEN-D0101, a selective I Kur blocker, prolonged the atrial effective refractory period (AERP) and decreased AF vulnerability in a dose-and rate-dependent manner in atrial tachycardia-induced remodeled canine atria (30,31). In human cardiomyocytes, XEN-D0101 prolonged AERP in AF-remodeled but not in non-remodeled tissue (32). However, experiments were conducted using a stimulation frequency of 1 Hz at which we predict no effect on APD and AERP based on this study; rapid stimulation rates at which I Kur -block induced prolongation of APD/atrial refractoriness would be expected were not reported.…”
Section: Relevance For Antiarrhythmic Drug Developmentmentioning
confidence: 71%
“…Mathematical simulations support these findings and suggest that I Kur blockers with rapid binding or slow unbinding kinetics have the strongest antiarrhythmic effects (22,29 Consistent with this study, XEN-D0101, a selective I Kur blocker, prolonged the atrial effective refractory period (AERP) and decreased AF vulnerability in a dose-and rate-dependent manner in atrial tachycardia-induced remodeled canine atria (30,31). In human cardiomyocytes, XEN-D0101 prolonged AERP in AF-remodeled but not in non-remodeled tissue (32). However, experiments were conducted using a stimulation frequency of 1 Hz at which we predict no effect on APD and AERP based on this study; rapid stimulation rates at which I Kur -block induced prolongation of APD/atrial refractoriness would be expected were not reported.…”
Section: Relevance For Antiarrhythmic Drug Developmentmentioning
confidence: 71%
“…Trwają badania kliniczne dotyczące kilku leków hamują-cych ultraszybki prąd potasowy (I Kur ) oraz innych inhibitorów nietypowych kanałów jonowych [673][674][675]. Leki te nie są jeszcze dostępne w praktyce klinicznej.…”
Section: Nowe Leki Antyarytmiczneunclassified
“…40,41 It has been assessed in a phase 1 study to establish the safety of modulating the Kv1.5 target in vivo and is currently being assessed in a proof-of-mechanism electrophysiology phase 1 study at multiple European sites. 42 XEN-D0103/S66913 is more potent and more selective than XEN-D0101 and has recently completed preclinical development. It causes a significant extension of the APD in atrial tissue, but has no effect on the APD in human ventricular tissue.…”
Section: Xention-d0101 and Xention-d0103/s66913mentioning
confidence: 99%